THE OWNERSHIP OF COPYRIGHTED WORK: A MALAYSIAN LEGAL PERSPECTIVE - Mohd Noor, Nor Azlina; Abd Aziz, Ahmad Shamsul; Mohd Noor, Nor Adila (Jurnal ’Ulwan, 2024)
A copyrighted work is a creation by an author, such as a literary, musical, or film work, that falls under section 7(1) of the Copyright Act 1987. The matter of ownership pertaining to copyrighted works that form part of an individual’s property is extensively debated during their lifetime. However, the matter regarding the issue of ownership concerning copyrighted works after the owner’s demise is hardly addressed. There is a misconception among the public that every copyrighted work automatically enters the public domain or becomes public property after the death of its owner. This article discussed the law regarding the eligibility of works to the copyright protection and the ownership which is applied during the lifetime of the author. This article aims to address the legal position of the copyrighted works ownership during the lifetime and after the death of the owner. The discussion adopts the qualitative doctrinal legal research method and uses content analysis method to analyse the data. This article concludes that the ownership of the copyrighted works owned by the original owner during his lifetime can be transferred to the legal heirs who can enjoy the rights associated with the copyright for a term of fifty years after the death of the owner. However, the principle under Copyright Act 1987 must be read together with the laws relating to the succession of deceased estates. This paper also suggests that it is high time for the relevant authorities to review the current duration of copyright protection by taking into account the life plus seventy years’ duration as applied in other countries such as Singapore and Australia for the benefit of the legal heirs.